Unveiling the factors influencing public knowledge and behaviours towards medication errors in Jordan: a cross-sectional study - Sura Al Zoubi; Lobna Gharaibeh; Enas A. Amaireh; Husam AlSalamat; Mohammad Ghassab Deameh; Amjad Almansi; Yaqeen Majed Al Asoufi; Hadeel Alshahwan; Zaha Al-Zoubi (BMC, 2024)
Abstract Background Medication errors are preventable incidents resulting from improper use of drugs that may cause harm to patients. They thus endanger patient safety and offer a challenge to the efficiency and efficacy of the healthcare system. Both healthcare professionals and patients may commit medication errors. Methods and objectives A cross-sectional, observational study was designed using a self-developed, self-administered online questionnaire. A sample was collected using convenience sampling followed by snowball sampling. Adult participants from the general population were recruited regardless of age, gender, area of residence, medical history, or educational background in order to explore their practice, experience, knowledge, and fear of medication error, and their understanding of this drug-related problem. Results Of the 764 participants who agreed to complete the questionnaire, 511 (66.9%) were females and 295 (38.6%) had a medical background. One-fifth of participants had experienced medication errors, with 37.7% of this segment reporting these medication errors. More than half of all medication errors (84, 57.5%) were minor and thus did not require any intervention. The average anxiety score for all attributes was 21.2 (The highest possible mean was 36, and the lowest possible was 0). The highest level of anxiety was seen regarding the risk of experiencing drug-drug interactions and the lowest levels were around drug costs and shortages. Being female, having no medical background, and having experience with medication errors were the main predictors of high anxiety scores. Most participants (between 67% and 92%) were able to recognise medication errors committed by doctors or pharmacists. However, only 21.2 to 27.5% of participants could recognise medication errors committed by patients. Having a medical background was the strongest predictor of knowledge in this study (P < 0.001). Conclusion The study revealed that the prevalence of self-reported medication errors was significantly high in Jordan, some of which resulted in serious outcomes such as lasting impairment, though most were minor. Raising awareness about medication errors and implementing preventive measures is thus critical, and further collaboration between healthcare providers and policymakers is essential to educate patients and establish effective safety protocols.